Analysis of survival and prognostic factors in amyotrophic lateral sclerosis: a population based study. Issue 1 (5th June 2007) - Zoccolella, S; Beghi, E; Palagano, G; Fraddosio, A; Guerra, V; Samarelli, V; Lepore, V; Simone, I L; Lamberti, P; Serlenga, L; Logroscino, G; ,
Abstract : Objective: To measure survivorship and predictors of prognosis of amyotrophic lateral sclerosis (ALS). Methods: Incident cases, diagnosed in the 1998–1999 period and classified according to the El Escorial criteria, were enrolled from a prospective population based registry established in Puglia, Southern Italy, with a reference population of 4 025 329. Cases were followed up until death or 30 June 2004. Results: We identified 130 incident cases of ALS while four were lost to follow-up. Median survival was 28 months from first symptoms and 16 months from diagnosis, while cumulative survivorship at 4 years was approximately 30%. Advanced age (>75 years: hazard ratio (HR) 7.5; 95% CI 1.9 to 29.6; p = 0.004) and bulbar or generalised (HR 1.8; 95% CI 1.1 to 3.0; p = 0.01) onset of symptoms were independent predictors of adverse survival. After stratifying patients according to site of first symptoms, age was a predictor of death among spinal (HR for patients aged >75 years compared with patients aged 45 years or less: HR 11; 95% CI 1.5 to 78.5; p = 0.01) but not among bulbar ALS (HR 4.5; 95% CI 0.4 to 46.5; p = 0.2). Among spinal onset cases, cases with predominant upper motoneuronal (UMN) involvement presented with a borderline significant better survivorship (HR 0.5; 95% CI 0.2 to 1.3; p = 0.1) Conclusions: Bulbar signs and advanced age among subjects with spinal onset were indicators of poor prognosis while El Escorial category at entry did not predict survival. Among subjects with spinal onset of the disease, a trend for a better survivorship of subjects with UMN signs was noted.